Children at risk of anaphylaxis: A mixed-studies systematic review of parents' experiences and information needs - Sholeh Rahman; Sarah A. Elliott; Shannon D. Scott; Lisa Hartling (Elsevier, 2022)
Objective: To explore parents' self-reported experiences and information needs regarding recognition and management of pediatric anaphylaxis. Methods: We searched Ovid Medline, Ovid PsychInfo, CINAHL Plus, the Cochrane Library, and grey literature to identify primary studies in English or French published since 2000. We used a mixed-method appraisal tool and convergent integrated approach to assess quality and synthesize data, respectively. Results: 43 studies were included (22 quantitative, 19 qualitative, and 2 mixed-method); 77% of studies had high methodological quality. Parents' experiences were categorized as: recognizing an anaphylactic reaction; managing and responding to a reaction; emotional impact of caring for a child at risk of anaphylaxis; and interaction with the health system and healthcare providers. Parents' information needs were categorized into themes relating to: gaps in knowledge and information; type of information desired; information sources; and information delivery format. Conclusion: Negative emotional experiences and a general lack of information were commonly reported by parents of included studies. Provision of relevant and comprehensible information may help parents to make informed decisions and manage reactions promptly. Innovation: The findings of this review are guiding the development of an innovative knowledge translation tool (KT) as part of a larger initiative of developing a suite of parent-focused KT tools for acute childhood conditions.